2021
DOI: 10.3390/plants10112419
|View full text |Cite
|
Sign up to set email alerts
|

Legume-Based Mobile Green Manure Can Increase Soil Nitrogen Availability and Yield of Organic Greenhouse Tomatoes

Abstract: Information about the availability of soil mineral nitrogen (N) in organic greenhouse tomatoes after the application of mobile green manure (MGM), and its impact on plant nutrient status and yield is scarce. Considering this knowledge gap, the effects of legume biomass from faba beans that are cultivated outdoors (FAB), or from feed-grade alfalfa pellets at two different doses (AAL = 330 g m−2; AAH = 660 g m−2) that were applied as MGM on the nutrition and yield of an organic greenhouse crop of tomatoes were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…In a recent study, Carricondo-Martínez et al (2022) [ 28 ] observed a reduced yield when using crop residues (C/N 15, yield 41.4 Tn/ha), composted goat manure (C/N 11, yield 41.0 Tn/ha), or composted vegetable waste (C/N 8.9, yield 43.2 Tn/ha) as compared with inorganic fertilizers used as a control (50 Tn/ha). While, in contrast, in other studies a higher production as compared with conventional mineral fertilization has been observed with the use of N-rich poultry manures or green manures [ 29 , 30 ]. Although the C/N ratio in our N-rich+C fertilizer was similar to that of the organic fertilizers used by Gatsios et al (2021) [ 29 ], we did not observe changes in productivity in any tested variety, perhaps because of the high fertility of our experimental field.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…In a recent study, Carricondo-Martínez et al (2022) [ 28 ] observed a reduced yield when using crop residues (C/N 15, yield 41.4 Tn/ha), composted goat manure (C/N 11, yield 41.0 Tn/ha), or composted vegetable waste (C/N 8.9, yield 43.2 Tn/ha) as compared with inorganic fertilizers used as a control (50 Tn/ha). While, in contrast, in other studies a higher production as compared with conventional mineral fertilization has been observed with the use of N-rich poultry manures or green manures [ 29 , 30 ]. Although the C/N ratio in our N-rich+C fertilizer was similar to that of the organic fertilizers used by Gatsios et al (2021) [ 29 ], we did not observe changes in productivity in any tested variety, perhaps because of the high fertility of our experimental field.…”
Section: Resultsmentioning
confidence: 80%
“…While, in contrast, in other studies a higher production as compared with conventional mineral fertilization has been observed with the use of N-rich poultry manures or green manures [ 29 , 30 ]. Although the C/N ratio in our N-rich+C fertilizer was similar to that of the organic fertilizers used by Gatsios et al (2021) [ 29 ], we did not observe changes in productivity in any tested variety, perhaps because of the high fertility of our experimental field. Similarly, Bénard et al (2009) [ 31 ] reported that low N supply rates had little impact on commercial tomato fruit yield.…”
Section: Resultsmentioning
confidence: 80%
“…In another study, faba bean was found to be the most suitable CC for improving the nutrient composition of organic kale, whereas ryegrass CC determined a higher kale biomass production, thus highlighting the importance of species selection (Thavarajah et al 2019). Gatsios et al (2021), comparing the effects of two different mobile green manures in organic greenhouse tomatoes, indicated that faba bean green manure is more effective than alfalfa pellets in increasing the plant available soil N and tomato leaf N concentration. Faba bean green manure also proved to be economically advantageous, since it enhanced yield, fruit number per plant and mean fruit weight more than alfalfa pellets.…”
Section: Zuo Et Al 2000mentioning
confidence: 99%
“…Seeking solutions with the aim to achieve healthier products through eco-friendly production systems, organic cultivation practices can be considered as a solution since inorganic N and synthetic agrochemicals are avoided. According to Gatsios et al [ 10 , 11 , 12 , 13 ], N supply in organic agriculture mainly relies on green and animal manures, composts, crop rotation with legumes, and utilisation of intercropping approaches. The introduction of the above-mentioned renewable N sources into agricultural production systems can also reduce contamination of water resources with nitrates [ 14 ] and increase the diversity of soil microbiota [ 15 ], thereby fostering soil nutrient availability, productivity, and health [ 16 ].…”
Section: Introductionmentioning
confidence: 99%